Case report: Possible acetaminophen poisoning complicated by puerperal sepsis - Arop M. D. Kual (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
Acetaminophen (paracetamol) toxicity is an important cause of morbidity and mortality worldwide. It is estimated that poisoning contributes to more than 1 million poisonings and up to half a million deaths each year, yet it is preventable and treatable. Acetaminophen toxicity is the second most common cause of liver transplantation worldwide. However, studies concerning poisoning in Botswana are scant, although it has been reported that poisoning contributes 6.7% of the total injuries and is ranked third next to falls and automobile accidents among external causes of mortality. This case report reviews the aetiology, evaluation, and treatment of acetaminophen overdose.